Jurnal Penggunaan Metode Scrum Dalam Membentuk Sistem Informasi Penyimpanan Gudang Berbasis Web - Sandi Pratama; Sulton Ibrahim; Muhammad Alfaqih Reybaharsyah (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2022)
Scrum method is a methodology that is included in agile software development. Scrum is considered capable of producing good quality software in accordance with the wishes of the user, can be used in large or small projects, and easy to adopt changes. Scrum activity stages include backlog, sprint backlog, daily scrum, sprint review, and sprint restropective products. Roles in Scrum include the product owner, Scrum Master, and Development Team. Scrum has stages that are structured and iterative, so that if the product in the first sprint does not adequately meet the needs, then the next sprint can be developed in accordance with the user's evaluation system. The results obtained on Scrum Method on Building Web Based Information System of Storage Inventory are proven to be able to overcome the changing requirements during the system development phase, producing products that are in accordance with the wishes of the user due to repeated reviews.